SAFTγ force field for the simulation of molecular fluids. 5. Hetero Group coarse-grained models of linear alkanes and the importance of intramolecular interactions - Galindo,A; Rahman,S; Lobanova,O; Jimenez-Serratos,G; Braga,C; Raptis,V; Muller,E; Jackson,G; Avendano,C (Journal of Physical Chemistry B, 2018)
The SAFT-γ Mie group-contribution equation of state [Papaioannou J. Chem. Phys. 2014, 140, 054107] is used to develop a transferable coarse-grained (CG) force-field suitable for the molecular simulation of linear alkanes. A heterogroup model is fashioned at the resolution of three carbon atoms per bead in which different Mie (generalized Lennard-Jones) interactions are used to characterize the terminal (CH3–CH2–CH2−) and middle (−CH2–CH2–CH2−) beads. The force field is developed by combining the SAFT-γ CG top-down approach [Avendaño J. Phys. Chem. B 2011, 115, 11154], using experimental phase-equilibrium data for n-alkanes ranging from n-nonane to n-pentadecane to parametrize the intermolecular (nonbonded) bead–bead interactions, with a bottom-up approach relying on simulations based on the higher resolution TraPPE united-atom (UA) model [Martin; , Siepmann J. Phys. Chem. B 1998, 102, 2569] to establish the intramolecular (bonded) interactions. The transferability of the SAFT-γ CG model is assessed from a detailed examination of the properties of linear alkanes ranging from n-hexane (n-C6H14) to n-octadecane (n-C18H38), including an additional evaluation of the reliability of the description for longer chains such as n-hexacontane (n-C60H122) and a prototypical linear polyethylene of moderate molecular weight (n-C900H1802). A variety of structural, thermodynamic, and transport properties are examined, including the pair distribution functions, vapor–liquid equilibria, interfacial tension, viscosity, and diffusivity. Particular focus is placed on the impact of incorporating intramolecular interactions on the accuracy, transferability, and representability of the CG model. The novel SAFT-γ CG force field is shown to provide a reliable description of the thermophysical properties of the n-alkanes, in most cases at a level comparable to the that obtained with higher resolution models.